Diversity, distribution and farmer preferences of Musa cultivars in Uganda - Gold, Cliford S.; Kiggundu, A.; Abera, A.M.K.; Karamura, D. (Cambridge University Press, 2002)
The East African highlands, home to more than 80 cultivated varieties of locally evolved bananas, constitute a secondary centre of banana diversity. Uganda is the leading producer and consumer of banana in the region and also enjoys the highest diversity of a group of bananas uniquely adapted to this region. These East African highland bananas comprise cooking and brewing types. The former is a staple for more than 7 million people and thus important for food security. Little is known about the distribution of the vast germplasm and this study was set up to help determine a distribution pattern and to understand the dynamics of cultivar change using farmers participatory appraisal methods. The study involved a guided interview with 120 farmers, at 24 sites throughout the banana-growing region of Uganda, to reveal cultivar diversity, proportions, distribution and preferences. Cultivar diversity ranged from 18 to 34 (mean = 26) cultivars per site, and from 4 to 22 (mean = 12.3), cultivars per individual farm. Such high diversity was attributed to a variety of end uses, better food security and the perception that each cultivar had a unique range of strengths and weaknesses. Highland banana (AAA-EA) represented 76% of total production while Kayinja (`Pisang Awak' subgroup) (ABB) contributed 8%; Ndiizi ('Ney Poovan' subgroup) (AB) 7%; Kisubi (`Ney Poovan' subgroup) (AB) 5%; Gros Michel (`Bogoya') (AAA) 2%; and plantain (AAB) 2%. Although 130 highland cultivars were recorded, only 10 constituted 50% of highland banana production while 45 cultivars were found at only 1 or 2 sites. A few cultivars showed more universal distribution and it is proposed that these may be the oldest and best performing local landraces.